Research on Heel Height of Women's Shoes Based on Walking Analysis (Journal of Fiber Bioengineering and Informatics, 2012)
The purpose of this study is to investigate how the different heel heights of women's shoes influencewalking according to walking analysis findings. Identifying heel heights that do not impair walkingcomfort were also investigated. Ten female university students were chosen as subjects and asked towear sample pumps with heel heights of 1.5, 3.5, 5.5, and 8.5 cm. The walking experiments focused onwalking movements, muscular activities of the lower limbs, and ground reaction at the point of impact.A questionnaire was then used to determine comfort levels while walking. The analysis discoveredthat the height of the heel was positively correlated with vertical movement, and that the subsequentchange in walking movements resulted in an increase in muscular activities and ground reaction, anda corresponding increase walking discomfort. It was also found that poor ratings were given for eachmeasurement item when a heel height of 8.5 cm was used, leading us to conclude that comfort duringwalking is compromised when the heel height increases beyond 6 cm.